CURRENT STATE OF ENDEMIC GOITER PREVALENCE AMONG THE FEMALE POPULATION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Endemic goiter in women represents a significant public health challenge, particularly in regions with iodine deficiency, as it is associated with a high risk of development and specific clinical and physiological features. This article examines the main factors contributing to the development of endemic goiter in women, including iodine deficiency, pregnancy-related physiological changes, nutritional habits, and insufficient awareness of iodine prophylaxis. Particular attention is paid to the role of increased iodine requirements during pregnancy, inadequate use of iodized salt, and limitations of risk-based screening approaches in primary health care. The analysis of these factors highlights the importance of improving preventive strategies and ensuring early detection of endemic goiter among women at the primary care level.
Keywords: Endemic goiter; iodine deficiency; women; pregnancy; iodine prophylaxis; early detection; primary health care